2018
DOI: 10.2174/0929867325666180226102358
|View full text |Cite
|
Sign up to set email alerts
|

RAS in the Central Nervous System: Potential Role in Neuropsychiatric Disorders

Abstract: Pre-clinical evidence supports a relevant role for ACE2/Ang-(1-7)/Mas receptor axis in several neuropsychiatric conditions, including stress-related and mood disorders, cerebrovascular ischemic and hemorrhagic lesions and neurodegenerative diseases. However, very few data are available regarding the ACE2/Ang-(1-7)/Mas receptor axis in human CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 0 publications
1
38
0
1
Order By: Relevance
“…21 Besides, ACE2, the receptor of SARS-CoV-2, 22 is a component of the renin-angiotensin system (RAS) which can be found in the central nervous system. [23][24][25] Animal studies indicated that RAS is related to stress and mood disorders. 24 25 Whether SARS-CoV-2 could infect the central nervous system and cause affect stress and emotional disturbances or not needs to be investigated.…”
Section: Main Findingsmentioning
confidence: 99%
“…21 Besides, ACE2, the receptor of SARS-CoV-2, 22 is a component of the renin-angiotensin system (RAS) which can be found in the central nervous system. [23][24][25] Animal studies indicated that RAS is related to stress and mood disorders. 24 25 Whether SARS-CoV-2 could infect the central nervous system and cause affect stress and emotional disturbances or not needs to be investigated.…”
Section: Main Findingsmentioning
confidence: 99%
“…The AT1R is also abundant in the pituitary and adrenal glands, corroborating this hypothesis [44]. Indeed, peripheral sympathetic nerve stimulation led to increased renin activity and therefore increased levels of Ang II [44]. Thus, prophylactic AT1R blockade outside and inside the blood-brain barrier in mice has been shown to reduce activation of the HPA axis and increase catecholamine synthesis [44].…”
Section: The Classical Raas Axismentioning
confidence: 83%
“…The concentration of AT1 receptors in the hypothalamic areas belonging to the hypothalamic-pituitary-adrenal (HPA) axis, including the area responsible for corticotrophin-releasing hormone (CRH) synthesis, is associated with Ang II signaling in response to stress [45]. The AT1R is also abundant in the pituitary and adrenal glands, corroborating this hypothesis [44]. Indeed, peripheral sympathetic nerve stimulation led to increased renin activity and therefore increased levels of Ang II [44].…”
Section: The Classical Raas Axismentioning
confidence: 91%
See 1 more Smart Citation
“…Так, було показано, що при застосуванні еналаприлу покращувалась ефективність лікування діабетичної нейропатії у щурів: збільшувалась швидкість проведення імпульсів моторними та чутливими нервовими волокнами, покращувалась теплова та вібраторна чутливість [10]. Беручи до уваги те, що РАС, завдяки центральним нейропротекторним властивостям, зменшує розміри інфаркту мозку, запалення, окислювального стресу і апоптозу нейронів [11], доцільно вивчити терапевтичні можливості еналаприлу при ХА. Мета роботи.…”
Section: Bukovinian Medical Herald V22 № 4 (88) р 48-53unclassified